R&D and Patents: An Attempt of Application of the Griliches’s Model in a Transitional Economy - Jasinski, Andrzej H.; Manikowski, Arkadiusz (School of Business and Management Institut Teknologi Bandung, 2012)
The main aim of this paper is to analyze relations between patent activity and R&D activity in Poland being a transitional economy in Central and Eastern Europe. The macro-perspective will be considered here. The paper begins with data on patents and R&D expenditures in the country in 1990-2010. Then the Griliches’s model is presented. The next section is devoted to an empirical verification of this model in Poland. Finally, there will be the main conclusions. Keywords: R&D, invention, patent, transitional economy